Tinjauan Literatur: Penerapan Nilai Islam pada Makanan dalam Ilmu Kesehatan - Sumule, Joshua Gunawan Anugra; Sihaloho, Serli; Pangaribuan, Ika S; Fathurohman, Oman (Penerbit Goodwood, 2025)
Purpose: This study aimed to conduct a comprehensive review of the existing literature on the relationship between Islamic values and dietary patterns, focusing on how these values affect individual and community health. Research methodology: A qualitative research methodology was employed using a literature review approach to analyze academic journal articles, books, and research reports published in the last five years. This method allows for an in-depth exploration of relevant studies and theoretical frameworks regarding Islamic dietary principles. Results: The findings indicate that the principles of halal and haram food significantly contribute to individual health by promoting cleanliness, preventing harmful substances, and fostering strong, social bonds. Halal food choices not only support physical health but also enhance spiritual well-being and social cohesion, especially through shared meals and communal eating practices. Conclusions: Overall, the application of Islamic values in food science offers strong potential to improve individual and public well-being. By adhering to halal principles and balanced eating, Muslims can achieve better physical and spiritual health outcomes. This review provides a solid foundation for developing programs and encouraging further research in the field. Limitations: This review is limited to literature published in the last five years, which may exclude older, but relevant, research on the topic. Contribution: Useful for education and socialization on healthy and halal food in the fields of health, social studies, and education, particularly for the younger generations.